Kepuasan Kerja Dipengaruhi oleh Lingkungan Kerja, Motivasi Kerja, dan Disiplin Kerja pada Karyawan Bank Mandiri Kantor Cabang Klandasan - Resvika Anggreani Sabri; Misna Ariani; Imam Arrywibowo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the influence between work environment variables, work motivation, and work discipline on job satisfaction of Bank Mandiri Klandasan Branch Office employees. This research uses a quantitative descriptive approach. The population in this study included 38 employees of Bank Mandiri Klandasan Branch Office. In this study using the census method, in which all members of the population are sampled. Data collection is done through literature review, interviews, and distributing questionnaires, processing data using SmartPLS to test the validity and reliability of the instrument. Based on the results of the t test, it shows that the work environment variable has a positive and significant effect on job satisfaction of Bank Mandiri Klandasan Branch Office employees. Work motivation variable has a positive and significant influence on employee satisfaction of Bank Mandiri Klandasan Branch Office. The work discipline variable has a negative and insignificant effect on job satisfaction of Bank Mandiri Klandasan Branch Office employees. It is recommended to increase interaction between staff, improve compliance with rules, and integrate other factors such as compensation or leadership in future research.